Vocational English Grammar: Computer Engineering Students’ Misformation Error Analysis on Auxiliary Verbs of Passive Voice in TOEIC Reading - Eka Putri, Rahmadila (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2025)
Vocational English in vocational college, such as polytechnic, is structured on their academic and professional potential. This notion also prevails on Computer Engineering students at State Polytechnic of Sriwijaya who learn English for 200 questions-TOEIC which is a widely recognized standardized test to assess the English proficiency in work-related setting. Particularly in TOEIC Incomplete Sentence in Reading section, a good mastery of grammar is necessary, yet students appear to be struggling due to the absence of rules in their mother tongue, resulting in error, for instance on misformation in passive-active questions. Therefore, this study is aimed to disclose their misformation error analysis to improve learning outcome particularly in passive-active form on Incomplete Sentence of TOEIC Reading. Research design for this study was quantitative descriptive with the population of 125 Computer Engineering students taking TOEIC preparation course (Bahasa Inggris 4) while the sample was 30 participants taken by purposive sampling technique. The research instrument was Multiple Choice Cloze Test consisted of 50 passive form questions adopted and adapted from Longman TOEIC Preparation dan Barron’s TOEIC. These questions were segmented equally for five common type of Tenses and discovered that the misformation error analysis in Simple Present Tense (33%; Good), Past Tense (29%; Good), Present/Past Continuous Tense (41%; Moderate), Future Tense (20%; Very Good), and Present Perfect Tense (41%; Moderate). In summary, Computer Engineering students at State Polytechnic of Sriwijaya’s error analysis was regarded “Good” (37%). However, they still need further practice with the grammatical pattern in passive voice across different tenses.Keywords: Vocational English, TOEIC, grammar, error analysis, passive voice